Attack of the black rectangles - King, A. S. (Amy Sarig), 1970- (Scholastic Press, 2022)
Mac's class is reading Jane Yolen's "The Devil's Arithmetic" in English class, but he's surprised when he opens his classroom copy one day to find some of the words blacked out. He thinks it must be a mistake, but when he and his classmates bring their concerns to their teacher and principal, they find themselves being ignored and dismissed. Someone doesn't want the kids to read the full story, so Mac and his friends band together to stand up against the censorship.